2007
DOI: 10.1159/000109215
|View full text |Cite
|
Sign up to set email alerts
|

Increase in β-Amyloid Levels in Cerebrospinal Fluid of Children with Down Syndrome

Abstract: Background: Individuals with Down syndrome (DS) invariably develop Alzheimer’s disease (AD) during their life span. It is therefore of importance to study young DS patients when trying to elucidate early events in AD pathogenesis. Aim: To investigate how levels of different amyloid-β (Aβ) peptides, as well as tau and phosphorylated tau, in cerebrospinal fluid (CSF) from children with DS change over time. The first CSF sample was taken at 8 months and the following two samples at 20–40 and 54 months of age. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 78 publications
1
32
0
Order By: Relevance
“…Interestingly, individuals with DS frequently display early onset AD and have increased Aβ serum levels [14, 15]. Furthermore, in the Ts65Dn mouse model of DS, which is trisomic for AβPP, a reduction of Aβ serum levels has been correlated to an improvement in learning and memory [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, individuals with DS frequently display early onset AD and have increased Aβ serum levels [14, 15]. Furthermore, in the Ts65Dn mouse model of DS, which is trisomic for AβPP, a reduction of Aβ serum levels has been correlated to an improvement in learning and memory [26].…”
Section: Discussionmentioning
confidence: 99%
“…The second hypothesis states that it is the expression of extra genes, regardless of their specific identity or function, that leads to disruption of genetic homeostasis, decreased buffering against environmental insults and ultimately, phenotypic alterations characteristic of DS [13]. Individuals with DS have been shown to have increased expression of brain AβPP and increased levels of amyloid-β in CSF, consistent with their predilection towards development of AD [14, 15]. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ␤ 2 AR and AMPA receptor are critical in normal brain functions. Thus, ␤ 2 AR internalization and degradation induced by A␤ could be generally implicated in various diseases with high levels of A␤ including AD, Down syndrome, and Parkinson disease (59,60).…”
Section: Discussionmentioning
confidence: 99%
“…With knowledge of the risk of impaired A ␤ 42 detection due to A ␤ oligomerization [13,14] , and as oligomeric A ␤ has been reported to be present in CSF [8][9][10][11] , it is intriguing to speculate if the decrease in A ␤ 1-42 measured by non-denaturing methods is -at least partially -due to the oligomerization of A ␤ in CSF. Several studies have reported differences in A ␤ detection depending on the method used, and the suggested explanation is epitope masking causing reduced detection when analyzing under non-denaturing conditions [13,15,21,[32][33][34] . The epitope masking can be explained by aggregation of A ␤ leading to hidden Cterminal epitopes in the hydrophobic core of aggregates [12] .…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy between denaturing and non-denaturing assays also suggests that the decline in A ␤ 1-42 observed in AD CSF can, at least to some extent, be explained by A ␤ oligomerization. Interestingly, longitudinally taken CSF samples from Down syndrome infants showed directly opposite A ␤ 42 patterns when analyzed under different assay conditions [33] . When calculating the A ␤ 42 oligomer ratio from these two analyses, non-denaturing Luminex [40] and denaturing Western blot [41] , an increase in the ratio from 8 months to 4.5 years of age was observed (p !…”
Section: Discussionmentioning
confidence: 99%